Proceedings of the Twenty-Second IEEE/ACM International Conference on Automated Software Engineering 2007
DOI: 10.1145/1321631.1321639
|View full text |Cite
|
Sign up to set email alerts
|

Modeling bug report quality

Abstract: Software developers spend a significant portion of their resources handling user-submitted bug reports. For software that is widely deployed, the number of bug reports typically outstrips the resources available to triage them. As a result, some reports may be dealt with too slowly or not at all.We present a descriptive model of bug report quality based on a statistical analysis of surface features of over 27,000 publicly available bug reports for the Mozilla Firefox project. The model predicts whether a bug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 264 publications
(190 citation statements)
references
References 17 publications
6
183
0
1
Order By: Relevance
“…analysis that required 30 days to operate [18]. The typical performance of our technique, which includes the cost of the 20% manual annotation burden and would take 1.3 h on average per release, is 0.0183-a 20% improvement over that figure.…”
Section: Resultsmentioning
confidence: 95%
“…analysis that required 30 days to operate [18]. The typical performance of our technique, which includes the cost of the 20% manual annotation burden and would take 1.3 h on average per release, is 0.0183-a 20% improvement over that figure.…”
Section: Resultsmentioning
confidence: 95%
“…In order to improve cooperation on a bug report between developers and users, many studies [10]- [14] have interviewed with OSS developers and users to understand the information needs for bug fixing. For example, through interviews with over 150 developers and 300 reporters of the Apache, Eclipse and Mozilla projects, Bettenburg et al [11] have found that steps to reproduce and stack traces are most useful in bug reports.…”
Section: How To Make a Good Bug Report?mentioning
confidence: 99%
“…Then we created two histograms: one is for the number of committed patches and another is for the number of changed status in bug reports. Then we used the median value in each histogram to define the threshold for categorizing into the four groups (14,15,22, and 23 committers in G1, G2, G3, and G4 respectively). We can consider committer's characteristics in each group as follows.…”
Section: Categorizing Each Committers Into Four Groups Depend-mentioning
confidence: 99%
“…Conventional development relies heavily on regression testing and reproducible defect reports; a testcase demonstrating the vulnerability makes it more likely that the defect will be fixed [29,30]. We…”
Section: Motivating Examplementioning
confidence: 99%
“…Although the vulnerability is real, it may not be obvious to developers how an untrusted user can trigger it. For example, setting posted newsid to "' OR 1=1 ; DROP 'news' --" fails to trigger it, instead causing the program to exit on line 4.Conventional development relies heavily on regression testing and reproducible defect reports; a testcase demonstrating the vulnerability makes it more likely that the defect will be fixed [29,30]. We…”
mentioning
confidence: 99%